Knowledge, attitude and practice on exposure to Bisphenol A among dental surgeons in Southern India - Harshit Atul Kumar; Crystal Runa Soans; PS Murali; MS Ravi; Keerthan Shashidhar; Shalin Shersha (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Bisphenol A (BPA) is a product in the manufacture of Bis-GMA, which is commonly used in dentistry, and is known to have a number of adverse effects. Objectives. The aim of this study is to evaluate to assess the knowledge, attitude and practice based on exposure and handling of BPA containing materials among dental surgeons for better understanding about the level of care rendered to the patients. Material and methods. A questionnaire survey was conducted on 400 dental surgeons in Southern India. The questionnaire consisted of 20 objective type questions out of which ten questions assessed knowledge and five questions assessed the attitude and five questions to understand the practice related measures taken by the dentist. The data collected were analysed using SPSS version 23. Results. A total of 402 responses were collected for this online questionnaire survey over a period of 2 months. It was found that females showed higher knowledge and attitude towards exposure to BPA which was statistically significant when compared to males. It showed that dentists with more than 20 years of practice had a higher level of knowledge. Though most of the groups agreed fairly on safety practice to be undertaken related to BPA exposure in their clinics, the ones with experience more than 20 years displayed the least positive attitude and dentists with 6-10 years of practice had the least positive behaviour among all. Conclusions. In spite of having a good knowledge regarding the harmful effects of BPA, dental surgeons are not very cautious while using materials containing them on a regular basis. Therefore, there is a need to enhance the awareness with the help of Continuing Dental Education programs or proper instructions on the packaging.